Pendampingan dalam Membentuk Kesadaran Digital di SDIE Hidayatul Ummah - Jauharotul Hanifa, Nabila; Multazam, Muhammad Yafi; Fathin, Na’imatul; Rizqi Mahfudi, Muhammad; Malikah, Nurul (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to determine assistance in forming digital awareness at the Hidayatul Ummah Magetan Islamic Elementary School. This is important to research because students need assistance in forming technological awareness. This research was carried out using a qualitative approach, data was collected by observation, interviews and documentation. Results show that student mentoring efforts play an important role in forming digital awareness, with a focus on understanding risks, responsible use of technology, and developing critical skills in facing digital challenges. Teachers also provide collaborative assistance with parents in successfully forming good digital awareness for children.